Design Development and Performance Evaluation of Phase Change Material (PCM) based Chiller for Raw Milk Cooling - Poonia, Surendra; Singh, A.K. (Annals of Arid Zone, 2023)
The phase change material (PCM) based milk chiller was designed anddeveloped at ICAR-Central Arid Zone Research Institute (CAZRI), Jodhpur, India. Theperformance evaluation of the developed box type well insulated chiller made of stainlesssteel 304 (SS 304) was carried out experimentally for different eutectic solutions andsalt hydrate viz. potable water (PW), propylene glycol, diethylene glycol, triethyleneglycol, and ammonium chloride (NH 4 Cl) at different concentrations (5-30%) are used forcooling energy storage. The initial temperatures of PW and propylene glycol at differentconcentrations were 25.8°C. The final temperatures of PW and propylene glycol atvarious concentration (5-30%) varies from -4.2°C to -14.9°C. The initial temperatures ofPW and diethylene glycol at different concentrations were 25.9°C. After freezing for 12hrs the final temperatures at various concentration (5-30%) varies from -4.1°C to -17.8°C.The initial temperatures of PW and triethylene glycol at different concentrations were25.8°C. After freezing for 12 hrs the final temperatures at various concentration (5-30%)varies from -3.9°C to -17.2°C. Similarly, the initial temperatures of PW and NH 4 Cl atdifferent concentrations were 25.8°C. After freezing for 12 hrs the final temperatures atvarious concentration (5-30%) varies from -3.7°C to -16.0°C. The chiller reduced milktemperature from 32.7°C to 11.4°C in about 120 minutes in case of PCM as potable water,32.6°C to 9.1°C in case of PW with 10% propylene glycol, 32.5°C to 8.5°C in case of PWwith 10% diethylene glycol, 32.6 to 8.8°C in case of PW with 10% triethylene glycol and32.5 to 9.3°C in case of PW with 10% NH 4 Cl concentration. The highest drop for PCM(PW+10% diethylene glycol) came to 9.9°C in 100 min followed by 8.7°C in the next 40min. The final temperature 10°C varied for about 2.5 hrs